Financial Exchange Rates and International Currency Exposures - Lane, Philip R; Shambaugh, Jay C (American Economic Review, 2010)
In order to gain a better empirical understanding of the international financial implications of currency movements, we construct a database of international currency exposures for a large panel of countries over 1990-2004. We show that trade-weighted exchange rate indices are insufficient to understand the financial impact of currency movements and that our currency measures have high explanatory power for the valuation term in net foreign asset dynamics. Exchange rate valuation shocks are sizable, not quickly reversed, and may entail substantial wealth redistributions. Further, we show that many developing countries have substantially reduced their negative foreign currency positions over the last decade. (F31, F32, G15)